Parasitic Load Correlates With Left Ventricular Dysfunction in Patients With Chronic Chagas Cardiomyopathy - de Oliveira, Maykon Tavares; Schmidt, André; da Silva, Maria Cláudia; Donadi, Eduardo Antônio; da Silva, João Santana; Marin-Neto, José Antônio (Frontiers in Cardiovascular Medicine, 2021)
Background: Chronic Chagas disease (CChD), one of the infectious parasitic diseases with the greatest social and economic impact upon a large part of the American continent, has distinct clinical manifestations in humans (cardiac, digestive, or mixed clinical forms). The mechanisms underlying the development of the most common and ominous clinical form, the chronic Chagas cardiomyopathy (CCC) have not been completely elucidated, despite the fact that a high intensity of parasite persistence in the myocardium is deemed responsible for an untoward evolution of the disease. The present study aimed to assess the parasite load CCC and its relation to left ventricular ejection fraction (LVEF), a definite prognostic marker in patients with CCC. Methods: Patients with CCC were clinically evaluated using 12-lead-electrocardiogram, echocardiogram, chest X-ray. Peripheral blood sampling (5 ml of venous blood in guanidine/EDTA) was collected from each patient for subsequent DNA extraction and the quantification of the parasite load using real-time PCR. Results: One-hundred and eighty-one patients with CCC were evaluated. A total of 140 (77.3%) had preserved left ventricular ejection fraction (of ≥40%), and 41 individuals had LV dysfunction (LVEF of <40%). A wide variation in parasite load was observed with a, mean of 1.3460 ± 2.0593 (0.01 to 12.3830) par. Eq./mL. The mean ± SD of the parasite load was 0.6768 ± 0.9874 par. Eq./mL and 3.6312 ± 2.9414 par. Eq./mL in the patients with LVEF ≥ 40% and <40%, respectively. Conclusion: The blood parasite load is highly variable and seems to be directly related to the reduction of LVEF, an important prognostic factor in CCC patients.